Thromboelastography for rapid diagnosis of heparin-like anticoagulant release during anaphylaxis-induced coagulopathy in systemic mastocytosis: a case report - Rajkumar Rajendram; Abdul Hadi Al-Qahtani; Farrukh Sheikh (Clinical Medicine)
Anaphylaxis can induce life-threatening coagulopathy by releasing various mediators from activated mast cells. These mediators directly affect coagulation and fibrinolytic pathways, increasing the bleeding risk. Diagnosis and management of anaphylaxis-induced coagulopathy remain challenging. We report a unique case of a 44-year-old man with undiagnosed systemic mastocytosis who developed peanut-induced anaphylactic shock, resulting in cardiac arrest. Laboratory tests revealed elevated serum tryptase and severe coagulopathy. Thromboelastography, a point-of-care viscoelastic monitoring (VEM) test identified the presence of heparin-like anticoagulants within minutes. Bone marrow examination subsequently confirmed isolated mastocytosis. This case highlights the potential of VEM for rapid diagnosis and management of coagulopathy in patients with anaphylaxis, potentially aiding in the identification of mast cell degranulation in undifferentiated shock. We suggest that VEM should be considered in the investigation of patients with suspected anaphylaxis-induced coagulopathy.